MODERN FINITE VOLUME METHODS SOLVING INTERNAL FLOW PROBLEMS - KAREL KOZEL; JAROSLAV FORT (TASK Quarterly, 2002)
The paper deals with explicit and implicit finite difference and mainly finite volume schemes that have been commonly used in last years for compressible and incompressible fluid flow problems. Mainly we mention schemes used for transonic flow computation (inviscid as well as viscous models) in internal and also external aerodynamics. We prefer modern schemes like RK multistage schemes, TVD and ENO schemes, implicit schemes or higher order schemes.